Protective effects of a natural product, paeoniflorin, on ischemia reperfusion injury on rat ovary tissue: histopathological, immunohistochemical, and biochemical study - Bayram, Pinar; Karamese, Selina Aksak; Erol, Huseyin Serkan; Ozdemir, Bengul; Toktay, Erdem; Salum, Cagatay (Informa UK Limited, 2023)
In this study, the main hypothesis is that paeoniflorin may inhibit some cellular processes such as oxidative stress and inflammation. For this reason, we aimed to investigate the potential protective effects of a natural compound, paeoniflorin, on rat model of ovarian ischemia-reperfusion injury by detecting the oxidative stress parameters and inflammatory process parameters. 42 female Wistar-albino rats were divided into 6 random groups. The rats were subjected to 3-hour ischemia and 3-hour reperfusion process. Then, paeoniflorin at doses of 25, 50 and 100 mg/kg were applied 30 min before the reperfusion. The levels of pro-inflammatory (IL-1-β, IL-6, TNF-α) and anti-inflammatory (IL-10, TGF-β) cytokines were measured by ELISA. Similarly, IL-6, IL-10, TNF-α, NF-κB p65) positivity rates were detected by immunohistochemical staining. Additionally, oxidative stress parameters (MDA, GSH, SOD) were measured by tissue biochemistry. Ischemia-reperfusion injury caused significant increase in the levels of SOD, MDA, TNF-α, IL-1-β, IL-6 and NF-κB p65, while paeoniflorin treatments improved the related parameters in a dose-dependent manner. As a conclusion, our findings support the evidence that paeoniflorin has a potential protective effects on ovarian ischemia-reperfusion injury. Further detailed studies should be performed to shed light the molecular mechanism of these protective effects.
Keywords: Biological Products; Interleukin-6; Tumor Necrosis Factor-alpha; Superoxide Dismutase; Ovary; NF-kappa B; Rats; Interleukin-10; Reperfusion Injury; Animals; Female; Rats, Wistar; Interleukin-1; 3. Good health